PENGARUH LATIHAN PUSH-UP DAN KADAR LEMAK TUBUH TERHADAP KETERAMPILAN SMASH DALAM PERMAINAN BULUTANGKIS KABUPATEN TAKALAR - Sudiadharma, Sudiadharma; Rahman, Abdul (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This experimental study aims to determine the effect of push-up training involving body fat levels on the smash skills of badminton games. Body fat levels consist of high and low. The experimental method uses a "two groups pre-test post-test design". The sample consisted of 20 Takalar Regency badminton players divided into two groups, each consisting of 10 Takalar Regency badminton players. The data analysis technique is the Tukey test analysis at a significance level of α = .05. The results of this study indicate that (1). There is an effect of push-up training between the initial test and the final test of low body fat levels on the skill of hitting smash in badminton game. This is evidenced by the results of the statistical analysis of the Tukey test, where Qhit = 7.14 > Qtab(0.05) = 4.33 (2). There was no push-up exercise between the initial test and the final test for high body fat levels on smash skills in badminton games. This is proven by using the tukey test, where Qhit = 0.99 < Qtab(0.05) = 4.33 (3). There is a difference in the effect of push-up training between the final test of low body fat content and the final test of high body fat content on smash skills in badminton games. The results of statistical analysis using the tukey test are proven, where Qhit = 9.45 > Qtab(0.05) = 4.33.